Distribution of butyltin compounds in Brazil's southern and southeastern estuarine ecosystems: assessment of spatial scale and compartments - Santos, Dayana Moscardi dos [UNESP]; Turra, Alexander; Rodrigues de Marchi, Mary Rosa [UNESP]; Montone, Rosalinda Carmela (Springer, 2016)
Butyltin compounds (BTs), including tributyltin (TBT) and its degradation products, dibutyltin and monobutyltin, have been found in a diversity of aquatic systems and causing toxic effects in target and nontarget organisms. They enter in coastal systems through different sources (as antifouling paints, industrial effluents, etc.) where they interact with biotic and abiotic components, and their distribution is commonly determined by the morphological and hydrodynamic conditions of the coastal systems. In this study, we discuss the contamination by BTs on a spatial scale (eight estuaries with three subareas each) and in different compartments of the estuaries (sediments, suspended particulate matter (SPM), and estuarine catfish tissues (liver and gills). Lower concentrations of BTs were found in the sediments (n.d. to 338 ng g(-1)) in comparison to studies before a ban of TBT in antifouling paints was enacted, mostly indicating an old input or preservation related with sediment properties and composition. For SPM samples (n.d. to 175 ng L-1) as well as in fish tissues (n.d. to 1426 ng g(-1)), the presence of these compounds was frequent, especially in the fish due to their movement throughout the estuaries and the potential to assess point sources of BTs. These results indicate that BTs persist in the environment, with variation in amounts between investigated estuaries and even at locations inside the same estuary, because of ideal preservation conditions, transport to remote areas, and input from different sources.
Keywords: Tributyltin; Catfish; Estuaries; Sediment